Congenital Disorders of Glycosylation with Emphasis on Cerebellar Involvement - Barone, Rita; Fiumara, Agata; Jaeken, Jaak (Seminars in Neurology, 2014)
Congenital disorders of glycosylation (CDG) are genetic diseases due to defective glycosylation of proteins and lipids. The authors present an update on these disorders affecting the central nervous system with a focus on cerebellar involvement. The rate of identification of novel CDG shows an exponential increase. Some 76 CDG are actually known, not taking into account the defects in glycan-modifying proteins. Neurologic involvement is present in the large majority of CDG. Screening methods are limited to serum transferrin isoelectrofocusing (for N-glycosylation disorders with sialic acid deficiency), and serum apolipoprotein C-III isoelectrofocusing (for core 1 mucin-type O-glycosylation disorders). Whole exome/genome sequencing is increasingly used in the diagnostic workup of patients with CDG-X. Treatment is greatly lagging behind because only one CDG is efficiently treatable (MPI-CDG). Cerebellar involvement is an important feature of PMM2-CDG, the congenital muscular dystrophies due to dystroglycanopathy, and SRD5A3-CDG. It has also been reported in some patients with ALG1-CDG, ALG3-CDG, ALG9-CDG, ALG6-CDG, ALG8-CDG, PIGA-CDG, DPM1-CDG, DPM2-CDG, B4GALT1-CDG, SLC35A2-CDG, COG1-CDG, COG5-CDG, COG7-CDG, and COG8-CDG.
Keywords: cerebellar; cerebellum; congenital disorders of glycosylation